2001
DOI: 10.1074/jbc.m108509200
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor-α Regulates the Expression of Inducible Costimulator Receptor Ligand on CD34+ Progenitor Cells during Differentiation into Antigen Presenting Cells

Abstract: The inducible costimulator receptor (ICOS) is a third member of the CD28 receptor family that regulates T cell activation and function. ICOS binds to a newly identified ligand on antigen presenting cells different from the CD152 ligands CD80 and CD86. We used soluble ICOSIg and a newly developed murine anti-human ICOS ligand (ICOSL) monoclonal antibody to further characterize the ICOSL during ontogeny of antigen presenting cells. In a previous study, we found that ICOSL is expressed on monocytes, dendritic cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 35 publications
3
33
0
Order By: Relevance
“…Importantly, the up-regulation of ICOS-L on human DCs, especially plasmacytoid DCs (pDCs), has already been shown to drive the generation of IL-10-producing T regs [26,28]. Furthermore, the up-regulation of ICOS-L on monocytes/DCs could be induced by inflammatory cytokines such as IFN-g [51], and possibly TNF-a [52], both potent cytokines implicated in sarcoidosis pathogenesis [5,53]. Notably, inflammatory cytokines such as TNF-a and IL-6 can act as a driving factor for the generation of IL-10-producing T regs through ICOS/ICOS-L interactions [27].…”
Section: Cd4mentioning
confidence: 99%
“…Importantly, the up-regulation of ICOS-L on human DCs, especially plasmacytoid DCs (pDCs), has already been shown to drive the generation of IL-10-producing T regs [26,28]. Furthermore, the up-regulation of ICOS-L on monocytes/DCs could be induced by inflammatory cytokines such as IFN-g [51], and possibly TNF-a [52], both potent cytokines implicated in sarcoidosis pathogenesis [5,53]. Notably, inflammatory cytokines such as TNF-a and IL-6 can act as a driving factor for the generation of IL-10-producing T regs through ICOS/ICOS-L interactions [27].…”
Section: Cd4mentioning
confidence: 99%
“…[34][35][36] Inhibition of NF-B activity by SN50, BAY 11-7082, and BAY 11-7085 blocked the ability of GM-CSF to promote cell survival in CTL-EN cells ( Figure 6C). No effect on cell survival was observed for the SN50M control peptide.…”
Section: Org Frommentioning
confidence: 99%
“…The ligand for ICOS (ICOS-L) shares only ~20% amino acid identity with CD80 and CD86. A soluble form of the ICOS receptor was generated and used, together with a subsequently developed mouse anti-human ICOS-L mAb 13C1 that has been generated by DNA vaccination [17], to characterize the ICOS-L. We found that ICOS-L is expressed on human antigen presenting cells of myeloid origin and on about 40% of peripheral blood CD19 + B cells [18]. Expression of ICOS-L was induced on monocytes after integrin-dependent plastic adhesion and was further upregulated by IFN-γ but not TNF-α.…”
Section: Icos Binds To a New Ligand (Icos-l) That Is Differentially Ementioning
confidence: 99%